2020
DOI: 10.1152/jn.00179.2020
|View full text |Cite
|
Sign up to set email alerts
|

The serotonin reuptake blocker citalopram destabilizes fictive locomotor activity in salamander axial circuits through 5-HT1A receptors

Abstract: Serotoninergic (5-HT) neurons are powerful modulators of spinal locomotor circuits. Most studies about 5-HT modulation focused on the effect of exogenous 5-HT and these studies provided key information about the cellular mechanisms involved. Less is known about the effects of increased release of endogenous 5-HT with selective serotonin reuptake inhibitors. Such molecules were shown to destabilize the locomotor output of spinal limb networks through 5-HT1A receptors. However, in tetrapods little is known about… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 154 publications
(268 reference statements)
0
11
0
Order By: Relevance
“…V0V: ventral commissural excitatory neurons positive for Dbx1, Homeobox even-skipped homolog protein 1 (Evx1), negative for Paired box protein 7 (PAX7), and involved in slow swimming in zebrafish and in left-right hindlimb [47][48][49], and tail muscles [8]. These spinal circuits generate multiple motor patterns, including the standing and travelling waves of axial motoneuron activity [11] that underlie the walking and swimming movements observed in vivo [10] (Figure 2G,H). Single cell recordings were also carried out in the spinal cord during fictive locomotion in the axial network [50] and limb networks [51].…”
Section: Pkd2l1: Polycystin 2 Like 1 Transientmentioning
confidence: 99%
See 1 more Smart Citation
“…V0V: ventral commissural excitatory neurons positive for Dbx1, Homeobox even-skipped homolog protein 1 (Evx1), negative for Paired box protein 7 (PAX7), and involved in slow swimming in zebrafish and in left-right hindlimb [47][48][49], and tail muscles [8]. These spinal circuits generate multiple motor patterns, including the standing and travelling waves of axial motoneuron activity [11] that underlie the walking and swimming movements observed in vivo [10] (Figure 2G,H). Single cell recordings were also carried out in the spinal cord during fictive locomotion in the axial network [50] and limb networks [51].…”
Section: Pkd2l1: Polycystin 2 Like 1 Transientmentioning
confidence: 99%
“…MLR Glut [14]; MLR GABA [112]; MLR ChAT [13,14,19]; RS Vglut2 [12]; RS GABA? [113]; axial Glut, Vglut2 [9,11]; axial ChAT [114]; axial GABA and Gly [9,50,115]; axial primary and secondary MNs [11,[115][116][117]; axial Rohon-Beard and Kolmer-Agduhr cells [115]; limb Glut [47,49]; limb GABA/Gly [48], limb MNs [47,55]; limb ChAT [118]; cutaneous [119,120] [75], the astrocytes. The salamander CNS is largely devoid of GFAP expressing cells intermingled with neurons both normally as well as after lesion, which may be one important reason behind the absence of injury responsive glial scar formation.…”
Section: Zebrafishmentioning
confidence: 99%
“…This caudal group mainly sends descending projections to the spinal cord, local projections to the brainstem, and a limited amount of ascending projections to the forebrain (Hornung, 2010 ). Finally, 5-HT neurons in the spinal cord project locally, send branches rostrally or caudally, or toward the ventrolateral border, and occasionally in the central canal (lamprey: Harris-Warrick et al, 1985 ; zebrafish: Montgomery et al, 2018 ; salamander: Flaive et al, 2020 ; turtle: Fabbiani et al, 2018 ; mouse: Ballion et al, 2002 ; Figure 1C ). In recent years, the use of genetic tools has allowed researchers to refine the characterization of 5-HT nuclei.…”
Section: The 5-ht Systemmentioning
confidence: 99%
“…Intriguingly, the effects of SSRI can be different from those of exogenous 5-HT. Whereas exogenous 5-HT increases rhythm stability, several studies reported that SSRI destabilizes fictive locomotion generated by the isolated spinal cord (lamprey: Christenson et al, 1989 ; mouse: Dunbar et al, 2010 ; zebrafish: Montgomery et al, 2018 ; salamander: Flaive et al, 2020 ). In some cases, in the same species, exogenous 5-HT decreases the frequency of fictive locomotor movements, whereas increasing the extracellular concentration of endogenous 5-HT increases the frequency (e.g., frog embryo: McLean and Sillar, 2004 ; salamander: Branchereau et al, 2000 ; Flaive et al, 2020 ).…”
Section: -Ht Modulation Of Locomotor Activitymentioning
confidence: 99%
See 1 more Smart Citation